Incidence, patterns of progression, and outcomes of preexisting and newly discovered brain metastases during treatment with anti–PD‐1 in patients with metastatic melanoma. Issue 23 (9th August 2019) - Schvartsman, Gustavo; Ma, Junsheng; Bassett, Roland L.; Haydu, Lauren E.; Amaria, Rodabe Navroze; Hwu, Patrick; Wong, Michael K.; Hwu, Wen‐Jen; Diab, Adi; Patel, Sapna Pradyuman; Davies, Michael A.; Hamerschlak, Nelson; et al.
Abstract : Background: Melanoma brain metastases (MBM) occur in up to 50% of patients with metastatic melanoma (MM) and represent a frequent site of systemic treatment failure for targeted therapies. However, to the authors' knowledge, little is known regarding the incidence, patterns of disease progression, and outcomes of MBM in patients treated with anti–PD‐1 immunotherapy. Methods: A total of 320 patients with MM who were treated with anti–PD‐1 at The University of Texas MD Anderson Cancer Center in Houston were reviewed. Analyses were performed to identify factors associated with brain metastasis–free survival and overall survival (OS) using Cox regression models. Results: The median age of the patients was 63.3 years. OS from the initiation of anti–PD‐1 therapy was not significantly different between patients without MBM prior to anti–PD‐1 compared with patients with prior MBM ( P  = .359). Among patients without prior MBM, 21 patients (8.6%) developed MBM during anti–PD‐1 therapy, 12 of whom (4.9%) presented with disease progression in the central nervous system (CNS) only. Developing MBM during or after therapy with anti–PD‐1 (hazard ratio, 4.70; 95% CI, 3.18‐6.93) was associated with shorter OS. Among patients with MBM prior to anti–PD‐1 treatment, 15 (20.0%) progressed in the CNS only and 19 (25.3%) progressed both intracranially and extracranially; at the time of the last data cutoff, 27 patients (36.0%) had not developed disease progression. Radiation necrosis occurred in 11.3% of patients (7 of 62 patients) in the group with a prior MBM who received stereotactic radiosurgery. Conclusions: Anti–PD‐1 therapy may change the natural history of patients with preexisting MBM. However, CNS failure during treatment with anti–PD‐1 is predictive of a worse prognosis compared with extracranial progression. The results of the current study support the activity of anti–PD‐1 in patients with MBM, although routine CNS imaging during therapy is warranted. Abstract : The incidence of new melanoma brain metastases occurring during or after therapy with anti–PD‐1 is reported to be 27.3% in the current study, and nearly one‐half of the patients with melanoma brain metastases experience intracranial disease progression only while receiving anti–PD‐1. No differences are noted with regard to overall survival among patients with and without brain metastases at the initiation of anti–PD‐1 therapy.